Microsensor systems for cell metabolism – from 2D culture to organ-on-chip. Issue 9 (5th April 2018) - Kieninger, Jochen; Weltin, Andreas; Flamm, Hubert; Urban, Gerald A.
Abstract : We discuss microsensors for cell culture monitoring from 2D culture to organ-on-chip systems, including sensor principles, fabrication and culture formats. Abstract : Microsensor systems for cell metabolism are essential tools for investigation and standardization in cell culture. Electrochemical and optical read-out schemes dominate, which enable the marker-free, continuous, online recording of transient effects and deliver information beyond microscopy and end-point tests. There has been much progress in microfluidics and microsensors, but the translation of both into standard cell culture procedures is still limited. Within this critical review, we discuss different cell culture formats ranging from standard culture vessels to dedicated microfluidic platforms. Key aspects are the appropriate supply of cells, mass transport of metabolites to the sensors and generation of stimuli. Microfluidics enable the transition from static to dynamic conditions in culture and measurement. We illustrate the parameters oxygen (respiration), pH (acidification), glucose and lactate (energy metabolism) as well as short-lived reactive species (ROS/RNS) from the perspective of microsensor integration in 2D and 3D cell culture. We discuss different sensor principles and types, along with their limitations, microfabrication technologies and materials. The state-of-the-art of microsensor platforms for cell culture is discussed with respect to sensor performance, the number of parameters and timescale of application. That includes the advances from 2D culture to the increasingly important 3D approaches, with specific requirements for organotypic microtissues, spheroids and solid matrix cultures. We conclude on the current progress, potential, benefits and limitations of cell culture monitoring systems from monolayer culture to organ-on-chip systems.